Mapping Global Joy: Descriptive Analytics of Subjective Well-Being from the World Happiness Report - Brandy, Susan (Jejaring Penelitian dan Pengabdian Masyarakat, 2024)
This article delves into the pursuit of happiness as a fundamental aspect of human existence, focusing on the exploration of factors contributing to subjective well-being (SWB). Drawing from the rich dataset obtained from the January 2019 release of the Gallup World Poll (GWP) and the World Happiness Report of 2019, spanning the years 2005 to 2018, our descriptive analytics offer a comprehensive analysis of global happiness. Through an examination of individuals' perceptions across diverse cultures and societies, this research elucidates key findings, revealing nuanced insights into the complex interplay of societal, economic, and personal elements that influence well-being on a global scale. This article contributes to a deeper understanding of the intricate fabric of happiness trends, patterns, and influencing factors, providing valuable insights for researchers and policymakers alike.